2011
DOI: 10.1038/mt.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function MITO-Porter, a Nano Carrier Integrating Both Efficient Cytoplasmic Delivery and Mitochondrial Macromolecule Delivery

Abstract: Mitochondrial dysfunction is associated with a variety of human diseases including inherited mitochondrial diseases, neurodegenerative disorders, diabetes mellitus, and cancer. Effective medical therapies for mitochondrial diseases will ultimately require an optimal drug delivery system, which will likely be achieved through innovations in the nanotechnology of intracellular trafficking. To achieve efficient mitochondrial drug delivery, two independent processes, i.e., "cytoplasmic delivery through the cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 36 publications
3
93
0
2
Order By: Relevance
“…Intracellular observations showed that the DF-MITO-Porter effectively delivered exogenous bioactive macromolecules into the mitochondria in living cells (Yamada et al, 2011;. Future study will include the packaging of MTS-modified MITO-Porter via endosome-fusogenic envelopes to achieve mitochondrial selective targeting in living cells using DF-MTS-modified MITO-Porter.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intracellular observations showed that the DF-MITO-Porter effectively delivered exogenous bioactive macromolecules into the mitochondria in living cells (Yamada et al, 2011;. Future study will include the packaging of MTS-modified MITO-Porter via endosome-fusogenic envelopes to achieve mitochondrial selective targeting in living cells using DF-MTS-modified MITO-Porter.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, we developed a Dual Function (DF)-MITO-Porter, which possesses mitochondriafusogenic inner envelopes and endosome-fusogenic outer envelopes (Yamada et al, 2011;. Intracellular observations showed that the DF-MITO-Porter effectively delivered exogenous bioactive macromolecules into the mitochondria in living cells (Yamada et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…The DF-MITO-Porter encapsulating DNase I was constructed as described in our previous reports (see Figure S1 in supplementary data for details) [21]. Complexed DNase I particles were first prepared with STR-R8, and were then coated with a mitochondria-fusogenic envelope.…”
Section: Construction Of Df-mito-porter Encapsulating Dnase Imentioning
confidence: 99%
“…The DF-MITO-Porter, which possesses mitochondria-fusogenic inner and endosome-fusogenic outer envelopes, has the ability to pass through endosomal and mitochondrial membranes via step-wise membrane fusion ( Figure 1) [21]. Octaarginine (R8) functions as a cell-uptake device [22,23] in the outer envelope and as a mitochondrial targeting device [12,24,25] in the inner envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation